Virtual planning and navigation for targeted excision of intraorbital space-occupying lesions: proposal of a computer-guided protocol. Issue 2 (February 2022) - Tel, A.; Murta, F.; Sembronio, S.; Costa, F.; Robiony, M.
Abstract: The purpose of this study was to present an innovative approach for the preoperative assessment and intraoperative targeted excision of masses occupying the intraorbital space based on multimodal image fusion, segmentation, virtual models, digital planning, and navigation. Nineteen patients were studied and underwent surgery using the presented workflow, in both open and endoscopic procedures. Three main scenarios were standardized for the application of computer-guided surgery: single masses of the superior-lateral compartment, single masses of the inferior-medial compartment, and multifocal masses. An operative protocol was devised, and the accuracy of the osteotomies was analysed. All patients were managed successfully by applying the same protocol. No intraoperative complications were reported. The accuracy of the osteotomies was evaluated as a surrogate endpoint for the overall precision of surgery, showing average discrepancies of <1 mm for lateral marginotomies and <0.5 mm for endoscopic osteotomies. This study outlines an operative workflow for the implementation of virtual models to excise orbital masses, enhancing in-depth preoperative understanding of the anatomical relationships within the orbital space and increasing precision in both open and endoscopic approaches.